2017
DOI: 10.1021/acs.jmedchem.6b01218
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Isaindigotone Derivatives To Downregulate c-myc Transcription via Disrupting the Interaction of NM23-H2 with G-Quadruplex

Abstract: Transcriptional control of c-myc oncogene is an important strategy for antitumor drug design. G-quadruplexes in the promoter region have been proven to be the transcriptional down-regulator of this gene. The transcriptional factor NM23-H2 can reactivate c-myc transcription by unwinding the G-quadruplex structure. Thus, down-regulation of c-myc transcription via disrupting G-quadruplex-NM23-H2 interaction might be a potential approach for cancer therapy. Here, a series of new isaindigotone derivatives were desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…36 Furthermore, silencing NME2 expression through siRNA, 27 and disrupting NME2 interaction with the NHEIII 1 /G4 complex using synthetic compounds, resulted in decreased CMYC expression. 37,38 Taken together, these results strongly suggest a direct role of NME2 in regulation of CMYC gene transcription.…”
Section: Roles Of Nme1 and Nme2 In Transcriptional Regulationmentioning
confidence: 66%
“…36 Furthermore, silencing NME2 expression through siRNA, 27 and disrupting NME2 interaction with the NHEIII 1 /G4 complex using synthetic compounds, resulted in decreased CMYC expression. 37,38 Taken together, these results strongly suggest a direct role of NME2 in regulation of CMYC gene transcription.…”
Section: Roles Of Nme1 and Nme2 In Transcriptional Regulationmentioning
confidence: 66%
“…Interestingly, we observed that the NME2-binding motif ( Fig. 4 a ) was within also within a hTERT promoter PG4-forming sequence, and because NME2 and promoter G4 interactions have been reported before ( 21 , 30 ), we asked whether the G4 structure played any role in hTERT repression by NME2. Oligonucleotide representing the PG4-forming sequence adopted mixed parallel/antiparallel G4 structures in solution ( Fig.…”
Section: Resultsmentioning
confidence: 87%
“…On the other hand, other isaindigotone derivatives developed by the same group were found to bind to both NM23-H2 and the G-quadruplex, and showed remarkable abilities in disrupting G-quadruplex–NM23-H2 interactions. They exhibited significant effects on c-myc -related processes in SiHa cells, including inhibiting transcription and translation, inhibiting cellular proliferation, inducing apoptosis, and regulating cell cycle [16].…”
Section: G-quadruplexes and Their Binding Proteinsmentioning
confidence: 99%
“…However, compared to developing inhibitors for a specific enzyme or protein, selective interaction with the G-quadruplex structures in particular genome regions is difficult to achieve. An alternative strategy for discovering novel G-quadruplex-related compounds is to interfere with the binding between G-quadruplex-forming sequences and the binding proteins [15,16,17]. Considering the fact that the shifts between various secondary structures in nucleic acids actually are regulated by several proteins binding to the nucleic acids [18,19,20,21], this alternative strategy seems attractive.…”
Section: Introductionmentioning
confidence: 99%